Contemporary structure in architecture - Michaels, Leonard (New York : Reinhold Publishing Corporation, 1950)
This book is concerned with structural potentialities in relation to architectural design; with what has been done and what can be done within the limits of reasonable economy. An architect does not often seek the cheapest method of construction without having regard to other factors such as appearance, maintenance, durability, etc.
I. Contemporary structure -- 1. The skeleton frame -- II. Structure in architectural design -- Appendix: Contemporary structural materials -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: BUILDING